Penal Policy and the Complexity of Criminal Law Enforcement: Introducing JILS 4(1) May 2019 Edition - Muhtada, Dani; Arifin, Ridwan (Faculty of Law, Universitas Negeri Semarang, 2019)
AFTER the previous edition of JILS raised the theme of â€œCrimes and Society: General Issues on Criminal Law in Indonesiaâ€, in this edition JILS wanted to explore various cases and developments in criminal law enforcement. The complexity of criminal law enforcement in many conditions presents a variety of debates, ranging from legality and non-retroactive principles of law which in certain cases find discrepancies between facts and existing theories. In addition, criminal law which is considered ultimum remedium and has the character of a double-edged sword, on the one hand protects the interests of victims and the public but on the other hand injures the rights of the accused, becomes very complex because of its relation to the protection of human rights. In order to provide the most up-to-date discourse in the development of criminal law enforcement, in this edition we take the theme â€œPenal Policy and The Development of Criminal Lawâ€. This theme provides a different perspective for readers relating to criminal law policy and formulation of criminal law enforcement. In this edition, we received a large number of articles sent to the editorial desk, therefore it requires considerable time in choosing, reviewing and giving our best feedback and comments to the authors. To highlight the development of criminal law enforcement, this Journal volume is dedicated to discuss several issues related to the penal policy and development of criminal law enforcement.